FACTORS INFLUENCING TEACHERS’ BELIEFS ON THE USE OF AUTHENTIC MATERIALS TO TEACH LISTENING - mandasari, berlinda (English Education:Journal of English Teaching and Research, 2017)
This research describes factors that influence teachers’ beliefs on the use of authentic materials to teach listening. This issue points out on what factors that shape their beliefs on authentic materials which are considered as good media to teach listening and support the learning and teaching practice. Two English teachers who constantly use authentic materials for listening skill are as the subject of this research. Observation, questionnaire and interview are administered to gain the data. The data are analyzed by using interactive model proposed by Miles and Huberman. The result shows that factors influencing teachers’ beliefs are: a) challenging points of authentic materials; b) easy access to authentic materials; c) the availability of the materials; d) students’ interest; e) worskop/training and personal experience. The result implies that some factors on using authentic materials have shaped teachers’ beliefs.